Nickel Supported MCM-Functionalized 1,2,3-Triazol-4-ylmethanamine: An Efficient Nano-particle-Heterogeneous Catalyst Activate for Suzuki Reaction - Hosseini, Samanesadat; Pourmousavi, Seied Ali; Mahdavi, Mohammad; Taslimi, Parham; Taslimi, Parham (Springer, 2022)
A novel, potent, efficient, and reusable heterogeneous nano-catalyst was prepared and grafted nickel into MCM-functionalized 1,2,3-Triazol-4-ylmethanamine (MCM-TA@Ni). The catalyst was characterized by various physico-chemical analysis such as Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, X-ray diffraction, thermo gravimetric analysis, Brunauer-Emmett-Teller (BET), atomic absorption spectroscopy, and energy dispersive X ray spectroscopy techniques. The catalytic activity of this recoverable nano-catalyst was studied for the carbon-carbon bond formation (Suzuki-Miyaura). [GRAPHICS] .
Keywords: Mcm-Functionalized 1,2,3-Triazol-4-Ylmethanamine; Suzuki-Miyaura Reaction; Heterogeneous Catalyst; Bi-Aryls; Ni Complex